Taking Stock of Risk Management Techniques for Sovereigns - Claessens, Stijn (World Bank, Washington, DC, 2012)
The author reviews the current state of affairs and thinking on external risk management for developing countries. He tries to identify the reasons behind the limited risk management by sovereigns. Perverse incentives arising from a too generous international safety net, limited access to international financial markets by developing countries arising from low creditworthiness, a limited supply of financial risk management tools suited to developing countries, and a poor supply of skills have inhibited risk management. Another constraint has been the limited attention given to the strategic objectives for risk management. Going forward, the author identifies actions by international financial markets, countries, and international financial institutions that can help improve risk management. These actions include GDP-indexed loans and efforts to develop price and weather indexes.